Imago dei. Et problem i de Fem Mosebøgers diskurs - Thompson, Thomas L. (Dansk Teologisk Tidsskrift, 2009)
Three times Genesis presents mankind as created in the image of God: the known is explained with the help of the unknown, as this narrative takes place in Feuerbach’s hall of mirrors. Do these texts speak of humanity created in God’s image or of the divine created in likeness of the human? Certainly the figure of Yahweh which dominates the narrative of the Pentateuch, reflects some of the most repulsive and objectionable of human traits. Does the narrative of the Pentateuch present us with its authors’ image of God or does it use ironic inversion to ultimately agree with Job that the God it narrates is false: one won from rumors, stories and tradition: a misunderstanding of the divine; that is, precisely the god as Israel of the past knew him. Taking its point of departure in my inaugural lecture, which dealt with the expression of Yahweh’s self-understanding, presented in the story of Moses at the burning bush, the first part of the lecture takes up the motif of images and likenesses of Yahweh in the stories of the golden calf, the feeding of Israel with manna and quail in the wilderness and the sending of the spies to the Valley of Eshkol. With the help of these narratives, I can then turn to the three-fold allegory of humanity as created in the image of God in Genesis 1-11 to compare this narrative figure of Yahweh with the concept of God in the Book of Job.